The role of Diplopoda litter grazing activity on recycling processes in a Mediterranean climate - Bertrand, M.; Lumaret, J. P. (Plant Ecology, 1992)
Variation in Diplopoda density and biomass were studied in mediterranean holm oak formations in order to estimate the impact of the feeding activity of these Arthropod s. Field and controlled experiments have shown the importance of the litter age and of the nature of leaves on the consumption rate. The con- sequences of faecal pellet restitution on microbial activity are discussed.
Keywords: diplopoda; edaphic macrofauna; faecal restitution; litter breakdown; sclerophyll formation